Educación financiera orientado a las finanzas personales para los estudiantes de bachillerato del colegio José María Vivar Castro - Pizarro Bonilla, Lizbeth Patricia (2022)
This research refers to financial education, which makes it possible for people to have the necessary knowledge to use financial products and services, manage their money efficiently, and make good financial decisions. In this regard, the objective of this research is to develop a financial education program for high school students of the private school "José María Vivar Castro". A descriptive and a quantitative approach were applied in this research to identify the financial knowledge that students possess. A survey of 26 questions based on various studies was used to collect the data. To obtain the results, 11 questions were taken as a reference to determine the students’ level of financial education knowledge according to the five levels established in the Program for International Student Assessment (PISA). It was evidenced that the students were at level 3; this means that they can identify financial products and services in relevant situations yet their knowledge of financial concepts is limited, which affects their decision-making. For that reason, it is important to design a financial education program that raises awareness about the proper management of personal finances from an early age. Once the training program about financial education was implemented and evaluated through a test, it was confirmed that the students improved from level 3 to level 5, which means that they can apply financial terms and products in relevant contexts now.